2017
DOI: 10.1175/jtech-d-16-0132.1
|View full text |Cite
|
Sign up to set email alerts
|

Ceilometer-Based Analysis of Shanghai’s Boundary Layer Height (under Rain- and Fog-Free Conditions)

Abstract: To investigate the boundary layer dynamics of the coastal megacity Shanghai, China, backscatter data measured by a Vaisala CL51 ceilometer are analyzed with a modified ideal curve fitting algorithm. The boundary layer height zi retrieved by this method and from radiosondes compare reasonably overall. Analyses of mobile and stationary ceilometer data provide spatial and temporal characteristics of Shanghai’s boundary layer height. The consistency between when the ceilometer is moving and stationary highlights t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Qualitatively, these patterns agree well with regional BLH climatology reported by Seidel et al (2012) for Europe and Guo et al (2016) for China. The seasonal patterns of MMLH also qualitatively agree with those derived using ceilometers over Shanghai (Peng et al 2017), London (Kotthaus and Grimmond 2018), Vienna (Lotteraner and Piringer 2016), and Vancouver (van der Kamp and McKendry 2010), and with that derived using micro-pulse lidar derived MMLH over Hong Kong (Yang et al 2013) and Beijing (Chu et al 2019). These studies suggest higher MMLH in the local summer and fall and lowest MMLH is found in winter.…”
Section: Data Selection and Mmlh Estimationsupporting
confidence: 82%
“…Qualitatively, these patterns agree well with regional BLH climatology reported by Seidel et al (2012) for Europe and Guo et al (2016) for China. The seasonal patterns of MMLH also qualitatively agree with those derived using ceilometers over Shanghai (Peng et al 2017), London (Kotthaus and Grimmond 2018), Vienna (Lotteraner and Piringer 2016), and Vancouver (van der Kamp and McKendry 2010), and with that derived using micro-pulse lidar derived MMLH over Hong Kong (Yang et al 2013) and Beijing (Chu et al 2019). These studies suggest higher MMLH in the local summer and fall and lowest MMLH is found in winter.…”
Section: Data Selection and Mmlh Estimationsupporting
confidence: 82%
“…Uncertainty of ALC‐derived Z ML is pronounced as aerosols may remain dispersed within the ABL even if turbulent mixing is reduced. This leads to the emerging residual layer often associated with Z ML (Haeffelin et al, ; Peng et al, ). Atmospheric stability (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The idealised profile method (Steyn et al, ) fits a theoretical profile to the observed attenuated backscatter (e.g. Eresmaa et al, ; ; Peng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al . () classify by cloud cover and then manually group days by relation to detected Z ML and potential residual layer to determine if the nocturnal detection results could be interpreted as the layer connected to the surface or the residual layer above. Harvey et al .…”
Section: Introductionmentioning
confidence: 99%